IN PURSUIT OF THE 40K BRANCHING RATIOS: K-CA AND 39AR-40AR DATING OF GEM SILICATES - Nagler T.F.; Villa I.M. (My University, 2000)
This paper presents combined 39Ar-40Ar and K-Ca analyses on gem quality, K-rich silicates: a muscovite and a sanidine, both from pegmatites. We attempted to directly determine the 40K branching ratio by comparing the radiogenic ingrowth of the daughter isotopes 40Ca* and 40Ar*. Sub-microgram amounts of Ca were analysed for isotopic composition with an external reproducibility of 0.03%. Ca analytics involved a 43Ca/48Ca double spike, miniaturised ion-exchange columns with a 1 ng Ca blank, and a Ta2O5 based loading reagent to allow for sub-microgram analyses. The sanidine gave clearly conflicting 39Ar-40Ar (461+/-6 Ma, 2σ, including uncertainty on the age monitor) and K-Ca (477+/-2 Ma) ages. The reason of the age discordance may be due to diffusive Ar losses; a low-temperature recrystallization is ruled out by the disordered Si-Al distribution. The muscovite sample gave nearly coincident 39Ar-40Ar and K-Ca ages applying currently recommended decay constants. Thus, analytically, this sample fits the requirements for a direct determination of the 40K branching ratio, which we calculate as BAr=0.1067, BCa=0.8933. These values are different from those generally used in geochronology, and closer to the values used in the physics community. It is clear, however, that the branching ratio proposed here needs to be verified by further investigation on supposedly ideal samples. The precision with which we are able to resolve the individual ages also reveals complications of the geological history even in gem quality silicates.
Keywords: K-CA DATING; 40K DECAY; BRANCHING RATIO; MADAGASCAR SANIDINE